2015
DOI: 10.1002/btpr.2157
|View full text |Cite
|
Sign up to set email alerts
|

Creating a completely “cell‐free” system for protein synthesis

Abstract: Cell-free protein synthesis is a promising tool to take biotechnology outside of the cell. A cell-free approach provides distinct advantages over in vivo systems including open access to the reaction environment and direct control over all chemical components for facile optimization and synthetic biology integration. Promising applications of cell-free systems include portable diagnostics, biotherapeutics expression, rational protein engineering, and biocatalyst production. The highest yielding and most econom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…This issue will need to be carefully addressed should the sensors be used outside of the laboratory setting. To this end, adjusting lyophilization conditions (40), increasing the intracellular lysis protein levels, and adding bactericidal agents that do not interfere with cell-free expression could feasibly be employed, however a careful further investigation of the issue is required.…”
Section: Discussionmentioning
confidence: 99%
“…This issue will need to be carefully addressed should the sensors be used outside of the laboratory setting. To this end, adjusting lyophilization conditions (40), increasing the intracellular lysis protein levels, and adding bactericidal agents that do not interfere with cell-free expression could feasibly be employed, however a careful further investigation of the issue is required.…”
Section: Discussionmentioning
confidence: 99%
“…Cell extracts were made using either E. coli BL21 Star (DE3) (Invitrogen, Carlsbad, CA) or ClearColi BL21 DE3 (Lucigen, Middleton, WI). Extract was produced as described previously with either LB, 2xYT, or TB fermentation media …”
Section: Methodsmentioning
confidence: 99%
“…Our lab demonstrated that we can efficiently produce a cytotoxic anticancer therapeutic, onconase, with a year old lyophilized cell extract (Salehi et al, 2016). Also, to create a portable CFPS platform to produce biotherapeutics and specially personalized/portable medicine and diagnostics, we reported how lyophilization can be used to sterilize and decontaminate cell extract without losing protein production capability (Smith et al, 2015). Additionally, a group of researchers recently reported a lyophilized, paper-based, in vitro system for synthetic gene network, which can expend the applications of the system into different areas including the clinic and global health (Pardee et al, 2014).…”
Section: Lyophilized Cell Extractmentioning
confidence: 99%